2021
DOI: 10.1177/13591045211005514
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy websites for children of parents with a mental illness

Abstract: Objective: This review of online mental health resources was conducted to evaluate and document the availability of mental health resources pertinent to the needs of children of parents with a mental illness (COPMI). This review identified available websites and analyzed the appropriateness of content and readability. Methods: We conducted an extensive 6-month review of websites with available mental health literacy content that may be found by COPMI searching for information. Web content was evaluated and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…In addition, Jorm's research found that increased MHL implies promise in its ability to increase resilience and possibly master more coping strategies (Jorm, 2012). This view has been supported by several studies (Fraser and Pakenham, 2009;Cavanaugh et al, 2021;Sullivan et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…In addition, Jorm's research found that increased MHL implies promise in its ability to increase resilience and possibly master more coping strategies (Jorm, 2012). This view has been supported by several studies (Fraser and Pakenham, 2009;Cavanaugh et al, 2021;Sullivan et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…The questionnaire was developed through literature searches of previously validated questionnaires. 7,10,23,[31][32][33][34]37,39,46,57 The content of the tool was prepared to gather information about the respondents' socio-demographic and mental health status, mental health literacy, online information-seeking behaviors, and item-related digital competency.…”
Section: Measurementsmentioning
confidence: 99%
“…Estas ferramentas online permitem um acesso fácil e rápido a informação sobre LSM e a recursos de intervenção em crise. Contudo, muitos dos conteúdos avaliados pelos autores tinham um âmbito geral e, como tal, apresentavam a lacuna de não abordar as circunstâncias singulares dos filhos de pessoas com doença mental (Cavanaugh et al, 2021).…”
Section: Estudos Internacionaisunclassified